T.H.R.O.B.V.S. Score – A Comprehensive Model to Predict the Surgical Complexity of Renal Cell Carcinoma With Tumor Thrombus - Wang, Kai; Liu, Zhuo; Hong, Peng; Qin, Yan-chun; Zhao, Xun; Zhang, Hong-xian; Liu, Cheng; Ge, Li-yuan; Ma, Lu-lin (Frontiers in Oncology, 2022)
Background: To propose a quantitative model for predicting the surgical complexity of patients with renal cell carcinoma (RCC) and venous tumor thrombus (VTT). Method: The clinical data of 226 cases of RCC with VTT in Peking University Third Hospital from January 2014 to August 2020 were retrospectively analyzed. Seven indicators were selected to establish the T.H.R.O.B.V.S. system, including alkaline phosphatase, tumor thrombus height, maximum tumor diameter, obesity, metastasis, bland thrombus, vascular wall invasion, and side. Each indicator was assigned 0, (1), and 2 points, and the total scores of 0 2, 3 5, and ≥6 were set as the low-, middle-, and high-risk groups, respectively. The surgical complexity was compared and validated among groups. Results: As the risk increased, the proportion of open surgery significantly increased (P<0.001). The operation time (P<0.001), intraoperative blood loss (P<0.001), blood or plasma transfusion (P<0.001), and hospitalization (P<0.001) increased significantly. The postoperative complications (P<0.001), including notable complications (≥Clavein-Dindo II, P<0.001), were significantly different, and similar trends were shown in the validation group. Conclusion: The T.H.R.O.B.V.S. scoring system is a quantifiable and satisfactory model to predict the surgical complexity and perioperative management of RCC with VTT.